TRADEMARK IMPERSONATION: REGULATION AND DISPUTE RESOLUTION - Shelvi Rusdiana (MIZAN, Jurnal Ilmu Hukum, 2022)
Intellectual property rights are created or arise from an idea to create a product or process that can be useful for human life. Intellectual property rights are also legal protection given to the results of human thought that are useful and have economic value. Understanding intellectual property itself requires comprehensive knowledge of what can be the object of intellectual property protection. A brand is an intellectual property identifier of a product or service owned by a company or individual. Violation related to registered trademark rights in Indonesia is an act that is against the applicable positive law. This study analyzes the regulation, legal protection of registered trademarks and dispute resolution. The research method used is a normative juridical research method using secondary data in the form of regulations related to brands and the results of previous studies. The results of this study indicate that a violation in the form of imitation of a registered mark can be subject to imprisonment and a fine. There are 2 (two) ways of resolving disputes regarding the imitation of the registered mark: filing a claim for compensation and terminating all activities related to the use of the mark. The lawsuit is submitted to the commercial court and can take arbitration or other alternative dispute resolution.